Building Entrepreneurial Motivation: Market Opportunities, Technology Innovation, and Business Partnerships for Future Business Success - Isnawati, Isnawati; Sabarini, Nur Endah; Hendayana, Yayan (Dinasti International Journal of Management Science, 2025)
Building Entrepreneurial Motivation: Market Opportunities, Technological Innovation and Business Partnerships for Future Business Success is an analysis of published works in the Entrepreneurship and Business Innovation course. To provide a foundation for future research, this article aims to generate hypotheses about the relationships between variables. Academic databases such as Google Scholar, Mendeley, and others are part of the research object. This research utilizes a literature review strategy based on the use of publicly accessible electronic resources, such as e-books and journals. Qualitative descriptive analysis was used. The following are the findings of the analysis: 1) The role of Market Opportunities in building entrepreneurial motivation for future business success; 2) The role of Technological Innovation in building entrepreneurial motivation for future business success; 3) The role of Business Partnerships in building entrepreneurial motivation for future business success